Exceptionally Warm and Prolonged Flow of Warm Deep Water Toward the Filchner‐Ronne Ice Shelf in 2017. Issue 13 (3rd July 2020) - Ryan, Svenja; Hellmer, Hartmut H.; Janout, Markus; Darelius, Elin; Vignes, Lucie; Schröder, Michael
Abstract: The Filchner‐Ronne Ice Shelf, fringing the southern Weddell Sea, is Antarctica's second largest ice shelf. At present, basal melt rates are low due to active dense water formation; however, model projections suggest a drastic increase in the future due to enhanced inflow of open‐ocean warm water. Mooring observations from 2014 to 2016 along the eastern flank of the Filchner Trough (76°S) revealed a distinct seasonal cycle with inflow if Warm Deep Water during summer and autumn. Here we present extended time series showing an exceptionally warm and long inflow in 2017, with maximum temperatures exceeding 0.5°C. Warm temperatures persisted throughout winter, associated with a fresh anomaly, which lead to a change in stratification over the shelf, favoring an earlier inflow in the following summer. We suggest that the fresh anomaly developed upstream after anomalous summer sea ice melting and contributed to a shoaling of the shelf break thermocline. Key Points: Three 4‐year‐long mooring time series show anomalously warm and prolonged inflow along the eastern flank of the Filchner Trough in 2017 Warm water persists on the shelf throughout winter and is associated with a fresh anomaly that leads to changes in the shelf density structure We hypothesize that the fresh anomaly originated from anomalous summer sea ice melt upstream and caused shoaling of shelf break thermocline